Identification of Socio-Ecological System of Seagrass Ecosystem in Bintan Regency - Nurul Dhewani Mirah Sjafrie, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Seagrass ecosystem is a productive ecosystem, inhabited by various economic and noneconomic value of biotas. Seagrass ecosystem on the east coast of Bintan Regency has been utilized since the 1970s. So far the relationship between the resources and the utilization of seagrass ecosystem in Bintan Regency has not been identified in detail. Both interactions will be influenced by other factors and will form a socio-ecological system (SES). The socio-ecological system is the interaction between the ecological unit and the social system that can be used in management. This study aims to: 1) identify the SES component and 2) the use of seagrass ecosystems in Bintan Regency. The research site is located in Teluk Bakau Village, Malang Rapat, Berakit and Pengudang. The questionnaires from 64 respondents which collected in September-December 2014 were used as a basic data for conducting focus group discussions (FGD). The SES components were analyzed descriptively, while to know the utilization of seagrass ecosystem, the result of FGD were weighted. The results showed that SES seagrass ecosystems formed a relation between natural resources, resource users, public infrastructure providers as well as public infrastructure. Seagrass ecosystem resources are fish, crab, cuttlefish and mollusck. The beneficiaries are traditional fishermen, fishermen, crackers makers, village collectors, district collectors, fisherman’s wife and domestic tourists. The four villages have a similar patterns of SES interaction. The interaction is shown by the role of seagrass ecosystem as a source of income, catch, catch handling and marketing.